Considerations Towards a Sustainable and Resilient Supply Chain: A Modelling Perspective - Nicoleta Tipi; Sara H. El Gazzar (International Business Logistics Journal)
Purpose: The development of models and application of modelling techniques are particularly important in supporting and enhancing our understanding of what happens in the supply chain, in gaining appreciation of what may happen in the future and what will be the most appropriate solution to work with. Research in modelling supply chain systems is however infrequent. Design/ methodology/ approach: Several theoretical and practical examples reported in the literature capture aspects of modelling and their benefits and limitations, still when approached from the point of view of the supply chain, the issues they managed to report on are however limited. Supply chains analysis are looking to respond to issues linked to effectiveness and efficiency, to sustainability, to resilience, to allow for opportunity for innovation and others. Findings: This research paper aims to provide an understanding of how modelling supply chains can be approached by evaluating modelling characteristics from the point of view of sustainability and resilience. Keywords: Sustainability, Supply Chain Management, Resilience, Modelling.